Removal of heavy metal ions from aqueous solutions by polymer-enhanced ultrafiltration / Nurul Huda Baharuddin - Nurul Huda, Baharuddin (2015)
The effects of pH, polymer concentration and metal ions feed concentration for four selected heavy metals, Zn(II), Pb(II), Cr(III) and Cr(VI), were investigated in this work; these metals were tested through a Polymer Enhanced Ultrafiltration (PEUF) system. Two conventional water-soluble polymers were selected, namely polyethylene glycol (PEG) and polyethyleneimine (PEI), and an unmodified starch as a biopolymer is proposed as an alternative binding reagent for four selected metal ions used for heavy metals’ removal from wastewater. Speciation profiles of Zn(II), Pb(II), Cr(III) and Cr(VI) species were obtained using available software to identify the soluble complexes of Zn(II), Pb(II),Cr(III), Cr(VI) ions and hydroxides ions (OH-) present in various charged ions, either as anions or cations, at a certain pH range. Potentiometric titration studies were carried out at first to investigate the potential interactions between the selected polymer and metal ions for complexation. Investigation through experimental works was done using ultrafiltration systems obtained by a laboratory ultrafiltration bench scale equipped with 10 kDa polysulfone hollow fiber membrane. The main operating parameter, namely the effects of pH, polymer composition and metal ions concentrations, were significantly affected by the retention coefficient and permeate flux conducted at constant pressure and flowrate. Unmodified starch and PEG as binding polymers performed complexation interactions due to non-ionic attraction of metal ions to the polymer on the molecular